Translation and opposition - Asimakoulas, Dimitris; Rogers, Margaret (Translating Europe, 2011)
Translation and Opposition is an edited volume that brings together cultural and sociological perspectives by examining translation through the prism of linguistic/cultural hybridity and inter/intra-social agency. In a collection of diverse case studies, ranging from the translation of political texts to interpreting in concentration camps, the book explores issues of power struggle, ideology, censorship and identity construction. The contributors to the volume show how translators, interpreters and subtitlers as mediators put their specific professional and ethical competences to the test by treading the dividing lines between constellations of `in-groups' and cultural or political `others'.